Swords Into Ploughshares: Life After the Secret War in Laos - Cho, Max (United States, 2013)
Max Cho’s film, is a look at one of the United States’ darkest historical moments, the Secret War on Laos. A powerful graphic style brings home the shocking details of a countryside covered with unexploded bombs. Cho puts a human face on this ongoing tragedy as he celebrates the initiative of the Laotian people, while also asking viewers to consider their role in eradicating bombs.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films